Pengaruh Pembelajaran Berbasis Daring Terhadap Hasil Belajar Mahasiswa Pendidikan Akuntansi Universitas Negeri Makassar - M. Yusuf A. Ngampo; Nuraisyiah; Nur Alinsa (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2023)
This study aims to determine the effect of online-based learning on student learning outcomes of Accounting Education at, the State University of Makassar. The variables of this research are online-based learning as the independent variable (X) and student learning outcomes as the dependent variable (Y). The population of this study was the 2018 and 2019 students of the Accounting Education Study Program consisting of 224 students, while the sample was 69 students who were taken using the proportionate stratified random sampling technique. Data collection is done by observation, questionnaires, and documentation. The data analysis used an instrument test and a hypothesis test. The results of this study indicate that online-based learning is included in the good category. Meanwhile, the student learning outcomes of Makassar State University Accounting Education are in a good category. From the results of simple linear regression analysis obtained online-based learning Y = 3.063 + 0.009X, which means that for each addition of 1 value of online-based learning, the value of learning outcomes has increased by 0.009. While the product-moment correlations obtained the coefficient of determination (r²) the value of r² = 0.070 or 7%, which means that online-based learning has a contribution to learning outcomes of 7 percent, and the remaining 93 percent is influenced by other factors. Meanwhile, the results of the t-test analysis obtained a significant value of 0.000 <0.05, which means that online-based learning has a significant effect on learning outcomes, thus the hypothesis is accepted.